1995
DOI: 10.1080/01635589509514407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemoprevention of oral cancer withspirulina fusiformis

Abstract: The blue-green microalgae Spirulina, used in daily diets of natives in Africa and America, have been found to be a rich natural source of proteins, carotenoids, and other micronutrients. Experimental studies in animal models have demonstrated an inhibitory effect of Spirulina algae on oral carcinogenesis. Studies among preschool children in India have demonstrated Spirulina fusiformis (SF) to be an effective source of dietary vitamin A. We evaluated the chemopreventive activity of SF (1 g/day for 12 mos) in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(93 citation statements)
references
References 15 publications
0
83
0
2
Order By: Relevance
“…Retinoids [85±87], b-carotene [88], vitamin E [89] and Spirulina fusiformis [90] have been shown to produce regression of oral leukoplakia, but the lesions recur soon after stopping the administration of the chemopreventive agents.…”
Section: Chemopreventionmentioning
confidence: 99%
“…Retinoids [85±87], b-carotene [88], vitamin E [89] and Spirulina fusiformis [90] have been shown to produce regression of oral leukoplakia, but the lesions recur soon after stopping the administration of the chemopreventive agents.…”
Section: Chemopreventionmentioning
confidence: 99%
“…It is characterized by 70% protein content and the presence of minerals, vitamins, amino acids, essential fatty acids (Mosulishvili et al, 2004), carbohydrates, essential fatty acids, sterols and blue pigments (phytocyanins), which contribute to increasing the protein and iron availability, and a low content of cholesterol and lipids (Jassby, 1983). Spirulina platensis acts as an immunostimulator (Mosulishvili et al, 2004) and has demonstrated anticarcinogenic (Mathew et al, 1995;Mishima et al, 1998) and antiviral effects (Ayehunie et al, 1998). In addition, certain Spirulina subspecies affect the immune system by enhancing phagocytic activity in macrophages (Jassby, 1988) and inhibiting allergic reactions in rodents (Hayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Spirulina (a single cell filamentous algae, richest source of protein, nature best food) is documented as; antioxidant & immunomodulator [14], hepatoprotective [15], nutraceutical [16], nephroprotective [17] neuroprotective [18], cardioprotective [19], anticarcinogenic [20], anti dyslipdeamic and anti hyperglycaemic activity [21]. Another study reported that insulin like protein is found in Spirulina [22].…”
Section: Introductionmentioning
confidence: 99%